Individual learning and social learning: Endogenous division of cognitive labor in a population of co-evolving problem-solvers - Myong-Hun Chang; Joseph E. Harrington (Administrative Sciences, 2013)
The dynamic choice between individual and social learning is explored for a population of autonomous agents whose objective is to find solutions to a stream of related problems. The probability that an agent is in the individual learning mode, as opposed to the social learning mode, evolves over time through reinforcement learning. Furthermore, the communication network of an agent is also endogenous. Our main finding is that when agents are sufficiently effective at social learning, structure emerges in the form of specialization. Some agents focus on coming up with new ideas while the remainder of the population focuses on imitating worthwhile ideas.
Keywords: 350; individual learning; social learning; organizational learning